ANALISIS KEMAMPUAN MENGERJAKAN SOAL HSK 3 MAHASISWA ANGKATAN 2024 PRODI PENDIDIKAN BAHASA MANDARIN FKIP UNTAN - Ariyanto, Vernando; Afrimonika, Yoanna; Khiong, Bun Yan (Universitas Tanjungpura, 2025)
HSK 3 is a test intended for test takers who have mastered the 600 most commonly used words and related grammar knowledge. The author chose to test the HSK level 3 test questions on the 2024 Class of Chinese Language Education Study Program, Faculty of Teacher Training and Education, Tanjungpura University, in order to analyze the differences in ability between class A and class B students. In the writing section, test takers must answer using Chinese characters, and in the second section, test takers must write Chinese characters based on the specified pinyin. the second part of the pinyin writing is still supported by the pole. In this study, the author used two research methods, namely the test method and literature study. From the total HSK 3 score analysis table, only 4 Class A students passed the HSK 3 test, while 13 Class B students passed the HSK 3 test. As a result, only 43% of the 2024 HSK 3 test passed.